Exercise guidelines for cancer survivors: consensus statement from international multidisciplinary roundtable - Campbell, Kristin L.; Wiskemann, Joachim (Medicine and science in sports and exercise, 2019)
The number of cancer survivors worldwide is growing, with over 15.5 million cancer survivors in the United States alone - a figure expected to double in the coming decades. Cancer survivors face unique health challenges as a result of their cancer diagnosis and the impact of treatments on their physical and mental well-being. For example, cancer survivors often experience declines in physical functioning and quality of life while facing an increased risk of cancer recurrence and all-cause mortality compared with persons without cancer. The 2010 American College of Sports Medicine Roundtable was among the first reports to conclude that cancer survivors could safely engage in enough exercise training to improve physical fitness and restore physical functioning, enhance quality of life, and mitigate cancer-related fatigue.